Comparative study on the new-old mortar interface deterioration after wet-dry cycles and heat-cool cycles. (30th May 2020) - Zuo, Shenghao; Xiao, Jia; Yuan, Qiang
Highlights: The bonding behaviors of the new-old mortar interface were studied. The deterioration of the new-old mortar interface after coupled cycles was studied. The microstructures of the new-old mortar interface were characterized. Abstract: A well-bonded interface between concrete substrate and repair materials is of great significance for the durable repaired concrete. In this paper, the performance of the new-old mortar interface and deteriorations after wet-dry or heat-cool cycles were investigated by mechanical tests and microstructural analyses. Slant shear test, four-point bending strength test, back scattering electron microscopy (BSEM), microhardness test and thermogravimetric analysis (TGA) were carried out to characterize the interface deterioration. The results show that the slant shear test is suitable for evaluating the new-old mortar bond strength. The constituents of repair mortars affect the bond strength, but have little impact on the bending strength of composite beams. After cycled treatments, coupled effect of wet-dry and heat-cool cycles result in severer deteriorations of new-old mortar interface than heat-cool cycles do. Effect of heat-cool cycles is mainly attributed to reduction of interlocking point, while reductions in both interlocking point and chemical bond force are responsible for the interface deterioration after coupled cycles. The microstructural analyses further reveal the characterization of the new-old interface zone.